2020
DOI: 10.3390/su12083398
|View full text |Cite
|
Sign up to set email alerts
|

The Tax Incentives in the IVTM and “Eco-Friendly Cars”: The Spanish Case

Abstract: This article describes research that was carried out regarding the tax incentives in Spain associated with the “eco-friendly car,” which are reflected in its share of taxes on motor-driven vehicles. The study focused on the electric vehicle, the hybrid, and the liquefied petroleum gas vehicle. First, the current regulatory framework was addressed. The maximum bonus limits were considered, as well as how each of 68 cities examined the incentives. The qualitative and quantitative differences among the Spanish ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…As indicated by [47] "gain environmental, energy, and economic benefits" or [48] "the important role of consumers in circular economy business models through the examination of consumers' acceptance of recycled goods", this system allows automatic and individual recycling; and as shown by the study of [49] this recycling can even help convert waste into energy. A circular economy based on the self-recycling of elements that today are wasted and thrown directly into the garbage can be very positive if combined with other measures in favor of the environment such as incentives for low polluting vehicles [50], new and more sustainable ways of transportation [51], which will undoubtedly result in a better welfare state [52].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by [47] "gain environmental, energy, and economic benefits" or [48] "the important role of consumers in circular economy business models through the examination of consumers' acceptance of recycled goods", this system allows automatic and individual recycling; and as shown by the study of [49] this recycling can even help convert waste into energy. A circular economy based on the self-recycling of elements that today are wasted and thrown directly into the garbage can be very positive if combined with other measures in favor of the environment such as incentives for low polluting vehicles [50], new and more sustainable ways of transportation [51], which will undoubtedly result in a better welfare state [52].…”
Section: Discussionmentioning
confidence: 99%
“…The use of these digital currencies backed by the central bank is one more step in the necessary digital transformation of societies [54] and, together with other measures such as those proposed by [55,56], will serve to promote this digital transformation, the one proposed by [26], since his study concluded that a CBDC would be accepted.…”
Section: Discussion: Cbdc and Its Implication For Payment Industry Opmentioning
confidence: 99%
“…Other studies focus on improving consumers' awareness of environmental concerns as a means of promoting green products and adding to the efficiency of environmental taxes [14] or the need for stricter regional government policies to increase the effectiveness of environmental taxes in combating pollution [15]. Since the EU member states have been trying to decrease air pollution levels and, in particular, CO 2 emissions, recent studies have focused on assessing the effectiveness of green taxes as incentives in promoting the use of environmentally friendly cars [16][17][18]. In the current study, environmental tax efficiency will be approached from a different perspective: that of increasing a country's fiscal space.…”
Section: Literature Reviewmentioning
confidence: 99%